Nursing Process in the Care of Bed Sores - Sharipova Shahlo Telmonovna (Лучшие интеллектуальные исследования, 2024)
This article provides information about nursing services for bedridden patients, the prevention of bedsores, and methods of caring for patients with bedsores.